2014
DOI: 10.2494/photopolymer.27.553
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Photovoltaic Feasibility of Pentaaryl [60]Fullerene in Bulk Heterojunction Architecture

Abstract: The photochemical process of pentaaryl [60]fullerenes (PAC 60 ) has been investigated by fluorescence and transient absorption spectroscopies, aiming at their use in bulk heterojunction organic photovoltaic (OPV). Fluorescence quenching was observed by adding C 60 into PAC 60 , where the intensity was decreased in an exponential manner. The photo-generated radical cation of PAC 60 was identified at 925 nm in the presence of electron acceptor. Motivated from the observed shallow molecular orbital levels of PAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Xe-flash time-resolved microwave conductivity (Xe-TRMC, 9 GHz) 27) experiment using a pseudo-sunlight white light pulse (0.3 mJ cm -2 pulse -1 ) as an excitation was conducted in order to study the photovoltaic performance of polymer: [6,6]-phenyl-C 61 -butyric acid methyl ester (PC 61 BM, purchased from Frontier Carbon Inc.) blends prior to device fabrication. 24,[28][29][30][31] The blend samples were prepared by drop-casting chlorobenzene (CB) solution of polymer:PC 61 BM onto quartz plate and dried under vacuum. The photoconductivity was obtained by P r /AP r , where P r , A, and P r , are the transient power change of reflected microwave power, sensitivity factor, and reflected microwave power, respectively.…”
Section: Synthesis Of Btt-mentioning
confidence: 99%
“…Xe-flash time-resolved microwave conductivity (Xe-TRMC, 9 GHz) 27) experiment using a pseudo-sunlight white light pulse (0.3 mJ cm -2 pulse -1 ) as an excitation was conducted in order to study the photovoltaic performance of polymer: [6,6]-phenyl-C 61 -butyric acid methyl ester (PC 61 BM, purchased from Frontier Carbon Inc.) blends prior to device fabrication. 24,[28][29][30][31] The blend samples were prepared by drop-casting chlorobenzene (CB) solution of polymer:PC 61 BM onto quartz plate and dried under vacuum. The photoconductivity was obtained by P r /AP r , where P r , A, and P r , are the transient power change of reflected microwave power, sensitivity factor, and reflected microwave power, respectively.…”
Section: Synthesis Of Btt-mentioning
confidence: 99%
“…For instance, Blom et al reported that P3HT:bisPCBM exhibited a 0.15 V higher V oc (0.73 V) than that of P3HT:PCBM, resulting in the improved PCE of 4.5% . More recently, indene C 60 bis-adduct (ICBA) and other bis-adduct [60]­fullerenes have emerged as the notable success of 56π fullerenes (PCEs, 4.7–6.5%). However, tris-, tetrakis-, or pentakis-adducts exhibited extremely low performance, due to the reduced short circuit current ( J sc ) and/or fill factor (FF). This results from a poor bulk heterojunction (BHJ) network and loose packing in the fullerene phase, indicative of the general trade-off issue between J sc (FF) and V oc in fullerene-based OPVs.…”
Section: Introductionmentioning
confidence: 99%